STRATEGI KOMUNIKASI PEMASARAN PADA MASA PANDEMI COVID-19 DI DINAS PARIWISATA DAN EKONOMI KREATIF KABUPATEN WAKATOBI SULAWESI TENGGARA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This study discusses the considerations of the Wakatobi Regency Tourism and Creative Economy Office in determining marketing communication strategies when dealing with the COVID-19 pandemic. Therefore, the purpose of this research is; to 1) to know the considerations of the Wakatobi Regency Tourism and Creative Economy Office in determining marketing communication strategies during the covid-19 pandemic. 2) find out the contribution of the marketing communication strategy to the interest of tourists to visit Wakatobi during the covid-19 pandemic. This type of research is a case study with a qualitative approach. Primary data sources were obtained through interviews with the marketing sector of the Tourism and Creative Economy Office of Wakatobi Regency. Data collection methods used are observation, interviews, and documentation. Using Miles and Huberman's data processing and analysis techniques, namely, data reduction, data presentation, and drawing conclusions. The consideration of the Wakatobi Regency Tourism and Creative Economy in determining the marketing communication strategy during the covid-19 pandemic is to carry out a marketing communication strategy that is able to attract potential tourists to visit Wakatobi and comply with the policies set by the government regarding tourism activities during the covid pandemic. -19. The marketing communication strategies carried out are interactive marketing, advertising, public relations, and event procurement. Marketing communication strategy has a very important position in supporting the increase in the number of tourists in Wakatobi. where the marketing communication strategy will make prospective tourists know information about Wakatobi, the existence of trust from prospective tourists, and the presence of tourist visits.